Planting, replanting and tree diversification in cocoa systems - learning about sustainable cocoa production: a guide for participatory farmer training - Asare, R.; David, S. (Forest and Landscape Denmark, 2010)
Cocoa production in West and Central Africa is low (200-700 kg/ha), as a result most cocoa farmers are not getting the full benefits from growing the crop. Studies conducted by the Sustainable Tree Crops Program (STCP) indicate that at present, a large number of farmers make a loss from growing cocoa. To turn this situation around, farmers need to intensify their cocoa cultivation. To help farmers intensify cocoa farms through best agronomic practices, the STCP in consultation with the Cocoa Research Institutes across West Africa developed a manual to provide technical guidance for farmers to establish and maintain cocoa farms. The planting, replanting and diversification manual is based on participatory learning and demonstration processes that promote mutual learning between farmers and experts. The training is based on five areas: (1) analysis of current farm situation, site selection for new cocoa establishment; (3) acquisition of planting materials for both cocoa and non-cocoa species; (4) preparation of the planting fields for both cocoa and non-cocoa species; and (5) plant diversification. This manual is divided into two sections. Section 1 contains bulletins that provide technical information on topics related to the five areas mentioned, and section 2 deals with corresponding demonstration learning exercises for participatory farmer training.